Masters Degree Programs in Instructional Technology - Association for Educational Communications and Technology, Washington, DC.; Association for Educational Communications and Technology, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This listing of 89 schools from around the world with master's degree programs in educational technology is based on the results of a survey completed by the International Division of the Association for Educational Communications and Technology in the fall of 1979. Countries represented in addition to the U.S.A. are Australia, Canada, Hong Kong, Korea, and Nigeria. Information for each entry includes admission requirements, graduation requirements, length of program, major fields or subjects, required courses, electives, grading evaluation, and curriculum administration and evaluation. The entries are alphabetically arranged by country, state, and school. A summary of the responses to 89 questionnaires is included, and a sample questionnaire is appended. (BK)
Availability: Association for Educational Communications and Technology, 1126 16th Street, NW, Washington, DC 20036 ($6.95).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum; Degree Requirements; Educational Technology; Foreign Countries; Higher Education; Masters Degrees; Masters Programs; Program Descriptions; Questionnaires; School Surveys; United States; Reference Materials, Directories/Catalogs.; Tests/Questionnaires.